Pyrolytic Modification of Avocado (Persea americana) Peel for the Enhancement of Cadmium(II) and Chromium(VI) Sorption Properties - Jarosław Chwastowski; Paweł Staroń (Applied Sciences, 2023)
The sorption process of chromium(VI) and cadmium(II) onto avocado peel (AP) and its pyrolyzed version (PAP) was carried out. The pyrolysis process was investigated in a tube furnace under inert gas conditions (argon) using a temperature equal to 750 °C. A constant mass of used materials and metal solution volume of 0.5 g and 20 cm3, respectively, were chosen for the investigation of the sorption process. Different isotherm models were fitted to describe the process parameters. According to the obtained results and the model that provided the best fit according to the correlation coefficient R2, the removal process is best described by the D-R model (R2 = 0.993 and 0.918; qd = 5.78 and 6.02 mg/g) for Cr(VI) and the Freundlich for Cd(II) ions (R2 = 0.999 and 0.911; Kf = 0.2712 and 0.2952 (mg1−(1/n)(dm(31/ng−1))) for AP and PAP, respectively). The highest level of adsorption capacities reached 6.0 (AP)–7.1 (PAP) and 9.7 (AP)–10.3 (PAP) mg/g for chromium and cadmium ions, respectively. The kinetic modeling showed that in all of the adsorption processes, the best-fitting model was the pseudo-second-order kinetic model, suggesting the occurrence of a chemical reaction between ions and the surface of the used materials.